Energy balanced routing algorithm for opportunistic network based on message importance - Zhigang CHEN; NBin'an YI; Jia WU (Tongxin xuebao)
A new routing algorithm MIEBR(message importance based energy balanced routing algorithm) was proposed. MIEBR measures the importance of messages. It determines message forwarding order and routing by message forwarding profit. When cache space is insufficient, MIEBR performs cache replacement based on message cache value. Simulation results show that, in cache space and energy constrained networks, MIEBR balances energy consumption of nodes, and reduces the latency of important messages. It outperforms other algorithms in delivery rate and latency.